2016
DOI: 10.1128/aem.02940-15
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus cereus NVH 0500/00 Can Adhere to Mucin but Cannot Produce Enterotoxins during Gastrointestinal Simulation

Abstract: Adhesion to the intestinal epithelium could constitute an essential mechanism of Bacillus cereus pathogenesis. However, the enterocytes are protected by mucus, a secretion composed mainly of mucin glycoproteins. These may serve as nutrients and sites of adhesion for intestinal bacteria. In this study, the food poisoning bacterium B. cereus NVH 0500/00 was exposed in vitro to gastrointestinal hurdles prior to evaluation of its attachment to mucin microcosms and its ability to produce nonhemolytic enterotoxin (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 44 publications
0
16
1
Order By: Relevance
“…This disagrees with prior studies in which NheB could not be detected in the supernatant of four B. cereus strains after they had been incubated in the presence of PGM (13,14). The authors concluded that Nhe was not detected due to insufficient bacterial concentrations or toxin degradation (13). In contrast to that, our studies proved that toxins accumulate in the supernatant and that this effect is not limited to a single toxin component.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This disagrees with prior studies in which NheB could not be detected in the supernatant of four B. cereus strains after they had been incubated in the presence of PGM (13,14). The authors concluded that Nhe was not detected due to insufficient bacterial concentrations or toxin degradation (13). In contrast to that, our studies proved that toxins accumulate in the supernatant and that this effect is not limited to a single toxin component.…”
Section: Discussioncontrasting
confidence: 99%
“…Little is known about the interaction of Bacillus cereus with the mucus layer or mucins. In vitro assays demonstrated adhesion of nonpathogenic and pathogenic B. cereus strains to porcine gastric mucin (PGM) (12)(13)(14). Furthermore, induction of fucosidase production suggests that B. cereus degrades and assimilates PGM (15).…”
mentioning
confidence: 99%
“…Nevertheless, under in vivo conditions, bacteria and potentially toxins, generally penetrate the outer, loosely adherent layer [55]. This could play a protective effect against the degradation by proteases present in the lumen.…”
Section: Discussionmentioning
confidence: 99%
“…During the pathogenic process of bacteria, attachment to external surfaces of a host is an important initial step in the colonization and subsequent occurrence of infection (Tsilia, Kerckhof, Rajkovic, Heyndrickx, & Van de Wiele, ). Indeed, without adhesion to its host, V. alginolyticus might not be able to persist at the initial infection focus, which would result in the absence of colonization and disease (Balebona et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, without adhesion to its host, V. alginolyticus might not be able to persist at the initial infection focus, which would result in the absence of colonization and disease (Balebona et al., ). Although bacterial adherence is one of the most active areas of study in the field of infectious diseases (Tsilia et al., ), the molecular mechanisms of V. alginolyticus adhesion have not been widely investigated.…”
Section: Introductionmentioning
confidence: 99%